2009
DOI: 10.1159/000257433
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Thymol on Suicidal Erythrocyte Death

Abstract: The antibacterial plant component thymol has antioxidant activity. Oxidative stress is known to activate Ca2+-permeable cation channels with subsequent Ca2+ entry, activation of Ca2+-sensitive K+ channels, cell shrinkage, cell membrane scrambling and phosphatidylserine exposure at the erythrocyte surface. Cell shrinkage and phosphatidylserine exposure are typical features of suicidal erythrocyte death or eryptosis. Eryptotic cells are cleared from circulating blood t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 73 publications
(76 reference statements)
0
21
1
Order By: Relevance
“…Earlier studies have indeed shown that excessive eryptosis contributes to the anemia of several disorders, such as iron deficiency [20], phosphate depletion [31], Hemolytic Uremic Syndrome [32], sepsis [33], malaria [14,[34][35][36][37][38][39], or Wilson's disease [40]. Furthermore, several anemia producing xenobiotics and endogeneous substances are at least partially effective through stimulation of eryptosis, such as cordycepin [41], amyloid peptides [42], lipopeptides [43], retinoic acid [44], amantadine [45], thymol [46], ciglitazone [47], amphotericin B [48], valinomycin [21], listeriolysin [49], copper [38], bismuth [50], tin [51], cadmium [52], selenium [53], vanadate [18], gold [54] and arsenic [55].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have indeed shown that excessive eryptosis contributes to the anemia of several disorders, such as iron deficiency [20], phosphate depletion [31], Hemolytic Uremic Syndrome [32], sepsis [33], malaria [14,[34][35][36][37][38][39], or Wilson's disease [40]. Furthermore, several anemia producing xenobiotics and endogeneous substances are at least partially effective through stimulation of eryptosis, such as cordycepin [41], amyloid peptides [42], lipopeptides [43], retinoic acid [44], amantadine [45], thymol [46], ciglitazone [47], amphotericin B [48], valinomycin [21], listeriolysin [49], copper [38], bismuth [50], tin [51], cadmium [52], selenium [53], vanadate [18], gold [54] and arsenic [55].…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone IIA may further potentiate the erj^jtotic effect of other eryptosis triggering xenobiotics [48,72,[79][80][81][82][83][84][85][86][87][88][89][90][91][92]. Accelerated eryptosis may lead to anemia [37] and adherence of phosphatidylserine-exposing erythrocjrtes to the vascular wall with the respective impairment of microcirculation [93][94][95][96][97].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, eryptosis is triggered or modified by a wide variety of substances [3,32,[55][56][57][58][59][60]. Several of the eryptosis-inducing diseases and xenobiotics have already been shown to influence the course of malaria, i.e.…”
Section: Discussionmentioning
confidence: 99%